Прецизійні засоби вимірювання характеристик теплового та оптичного випромінювання - Шабашкевич, Б.Г.; Добровольський, Ю.Г. (Актуальні проблеми транспортної медицини, 2005)
Авторы в своей работе представили разработанные научно-производственной фирмой «Тензор» прецизионные средства
измерения характеристик теплового и оптического излучения такие, как термоэлектрический преобразователь, чувствительный в спектральном диапазоне 0,2-25,0 мкм; портативный термостабилизований цифровой радиометр РАТ; излучатели АЧТ; поверхностно-барьерный фотодиод; радиометр УФР-21; фотометр цифровой ТЕС 0693; пулевой термометр «Тензор-41», что обеспечивают современный уровень проведения санитарно-гигиенических исследований при аттестации рабочих мест. For providing the control of labour conditions, including means of transport as well as ecological monitoring the research - and- manufacturing firm "Tenzor" has developed several devices for the sanitary-and-hygienic expertise performance during certification of the working places. The devices under description can measure distribution of thermal and optical radiation, for example thermal electrical converter sensible in a spectral range 0,2 - 25 мm (РАТ-2П); portable thermostable digital radiometer PAT, radiator АЧТ, surface-barrier photodiode, radiometer УФР-21; ph digital photometer TEC 0693, ball-shaped thermometer Тензор-41. They all are available in a portable variant and can provide a modern level of both researches and sanitary tests conducting.
Devices are executed in of the same type
portable corps, the indication is had on the base of liquid-crystal displays, the combined feed, are characterized by low consumable power.
Power photometry, metrology, labor protection, medicine, agriculture, balneology, is the application domain of devices heat-and- power engineering, building, machinery construction. Devices are widely used in hygiene and sanitary and medical establishments of countries UIG.